(untitled) (Research, Society and Development, 2020)
Due to the disordered urban growth since the 1970s and the occupation of flooded areas, the city of Belém suffers consequences with the precarious urban drainage network associated with high rainfall. The purpose of this work is to relate the climatological variables (precipitation, temperature, humidity, sunshine, evaporation) with urbanization in Belém and the climatic phenomena El Niño and La Niña, using the non-parametric statistical tests of Mann-Kendall and Spearman. The study period was from 1970 to 2010, which highlights the constant transformation of the city and the growth of the urban fabric. The urban growth of Belém in this period was approximately 85% with a considerable decrease in green areas. The temperature had an average increase of 0.5ºC in the period. The occurrence of El Niño and La Niña is directly related to the maximum and minimum extremes of precipitation, but it does not coincide with the rise in temperature when it is related to the Oceanic Niño Index (a) (ION). In the city of Belém, temperature may be associated with changes in the natural environment and with an increase in the average global temperature. When applying the tests (Mann-Kendall and Spearman) on climatological variables, it is observed that precipitation and temperature have a significant tendency to increase, and consequently the humidity and evaporation of decay, only insolation did not show a significant trend. The changes in climatological variables presented in this work may be related to the increase in urbanization in Belém in the last forty years. The intensification of urbanization combined with the absence of urban planning causes an intensification of flooding points and a decrease in thermal comfort.